Modern Trends in Mediatisation of Culture in a Digital Society - Baigozhina, Dana O.; Ibrayeva, Elmira E.; Duisengazy, Serikzat M.; Takhan, Serik Sh.; Zhanysbayeva, Akniyet P. (International Journal of Criminology and Sociology, 2022)
The establishment of a new dominant technological order is caused by the growth dynamics of the digital media space – an important component of the global media space, the development of which is a natural stage in the era of electronic communications. The media space is a sophisticated self-organising system and is a part, a subsystem of the information and communication universe as a set of all systems, one way or another related to communication processes. The novelty of the study is determined by the postulate that the media space constitutes a component of the global space of social life of people, generates and organises the production and consumption of information in various forms of social communication; this is a special reality. The authors show that its development is facilitated by the growth of the variety of communication technologies that accompanied the historical and cultural development of society. The paper shows that the media space is described by several components that determine social life: the technosphere built on information and communication technology; an infosphere based on information network highways; socio-infosphere, which includes information flows and organised structures that control the processes of their creation and consumption and affect the state of social intelligence. The practical significance of the study is that the media space is not only a retransmitter of information, but also its producer, in connection with which it acts as a complex, global system that contains all socio-cultural components capable of developing information prerequisites and requests and catering to the information needs by all possible communication means.